IMPROVE trial: A randomized controlled trial of patient-controlled analgesia for sickle cell painful episodes: rationale, design challenges, initial experience, and recommendations for future studies. (April 2013) - Dampier, Carlton D; Smith, Wally R; Wager, Carrie G; Kim, Hae-Young; Bell, Margaret C; Miller, Scott T; Weiner, Debra L; Minniti, Caterina P; Krishnamurti, Lakshmanan; Ataga, Kenneth I; Eckman, James R; Hsu, Lewis L; et al.
Background: The hallmark of sickle cell disease (SCD) is pain from a vaso-occlusive crisis. Although ambulatory pain accounts for most days in pain, pain is also the most common cause of hospitalization and is typically treated with parenteral opioids. The evidence base is lacking for most analgesic practice in SCD, particularly for the optimal opioid dosing for patient-controlled analgesia (PCA), in part because of the challenges of the trial design and conduct for this rare disease. Purpose: The purpose of this report is to describe our Network's experiences with protocol development, implementation, and analysis, including overall study design, the value of pain assessments rather than 'crisis' resolution as trial endpoints, and alternative statistical analysis strategies. Methods: The Improving Pain Management and Outcomes with Various Strategies (IMPROVE) PCA trial was a multisite inpatient randomized controlled trial comparing two PCA-dosing strategies in adults and children with SCD and acute pain conducted by the SCD Clinical Research Network. The specified primary endpoint was a 25-mm change in a daily average pain intensity using a Visual Analogue Scale, and a number of related pain intensity and pain interference measures were selected as secondary efficacy outcomes. A time-to-event analysis strategy was planned for the primary endpoint. Results: Of 1116 individuals admitted for pain at 31 participating sites over a 6-month period, 38 were randomized and 4 withdrawn. The trial was closed early due to poor accrual, reflecting a substantial number of challenges encountered during trial implementation. Limitations: While some of the design issues were unique to SCD or analgesic studies, many of the trial implementation challenges reflected the increasing complexity of conducting clinical trials in the inpatient setting with multiple care providers and evolving electronic medical record systems, particularly in the context of large urban academic medical centers. Lessons learned: Complicated clinical organization of many sites likely slowed study initiation. More extensive involvement of research staff and site principal investigator in the clinical care operations improved site performance. During the subsequent data analysis, alternative statistical approaches were considered, the results of which should inform future efficacy assessments and increase future trial recruitment success by allowing substantial reductions in target sample size. Conclusions: A complex randomized analgesic trial was initiated within a multisite disease network seeking to provide an evidence base for clinical care. A number of design considerations were shown to be feasible in this setting, and several pain intensity and pain interference measures were shown to be sensitive to time- and treatment-related improvements. While the premature closure and small sample size precluded definitive conclusions regarding treatment efficacy, this trial furnishes a template for design and implementation considerations that should improve future SCD analgesic trials.